Psychometric Property Test on Burdened Care Caregiver Scale-Thai Version for Schizophrenia and Co-occurring Methamphetamine Use - Imkome , Ek-Uma (Current Overview on Disease and Health Research Vol. 8, 2022)
This chapter aims to present the psychometric properties of the Thai version of the Impact and Burden of Care Scale for Caregivers of Persons with Schizophrenia and Co-occurring Methamphetamine Use (TIBSCSM). In this study, 142 caregivers of persons with schizophrenia and co-occurring methamphetamine use response were tested by Kaiser–Meyer–Olkin (KMO), and Bartlett's test of sphericity tested the adequacy of the item correlation matrix. The theoretical model underwent a second-order confirmatory factor analysis (CFA) test. The 32-item TIBSCSM showed convergent validity correlations with two quality-of-life measures. Additionally, KMO=0.9, Bartlett’s Test of Sphericity X2=5248.5, df=496, p<0.001, CVI =1, and internal consistency reliability was high (\(α\)=0.9). The CFA has shown that the theoretical models support the findings (X2=325.2, df=287, p<0.001, RMSEA=0.0, CFI =0.9). The TIBSCSM scale has the potential to benefit psychiatric nurses and psychiatric care teams in nursing, research, education, and clinical determination by measuring the impact and care burden of caregivers of people with schizophrenia and methamphetamine use.